2013
DOI: 10.1371/journal.pone.0062885
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of the Fecal Microbiota in Patients with Nonalcoholic Steatohepatitis – A Longitudinal Study

Abstract: BackgroundThe human gut microbiota has profound influence on host metabolism and immunity. This study characterized the fecal microbiota in patients with nonalcoholic steatohepatitis (NASH). The relationship between microbiota changes and changes in hepatic steatosis was also studied.MethodsFecal microbiota of histology-proven NASH patients and healthy controls was analyzed by 16S ribosomal RNA pyrosequencing. NASH patients were from a previously reported randomized trial on probiotic treatment. Proton-magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
238
2
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(272 citation statements)
references
References 43 publications
22
238
2
5
Order By: Relevance
“…Initial evidence for an altered gut microbiota in obesity is the observation by Ley et al that ob/ob mice (9) and obese patients (10) exhibit reduced abundance of Bacteroidetes and proportionally increased abundance of Firmicutes. Altered gut microbiota in obesity was also observed by other researchers, although the observed changes were usually different (11)(12)(13)(14)(15)(16)(17)(18), and frequently opposite (12)(13)(14)(15)(16)(17)(18) to the observations of Ley et al Note that only three studies stated that the enrolled patients and controls did not take antibiotics in the 3-mo period before sample collection; and all three studies reported an increased Bacteroidetes/Firmicutes ratio in the gut of obese patients (12)(13)(14)19) (Table 1). Our group paid particular attention to proton pump inhibitors and histamine receptor antagonists (14,19) as these agents are known to affect Firmicutes (20).…”
Section: Hypothetical Mechanism 1: Elevated Energy Extraction In the supporting
confidence: 61%
See 1 more Smart Citation
“…Initial evidence for an altered gut microbiota in obesity is the observation by Ley et al that ob/ob mice (9) and obese patients (10) exhibit reduced abundance of Bacteroidetes and proportionally increased abundance of Firmicutes. Altered gut microbiota in obesity was also observed by other researchers, although the observed changes were usually different (11)(12)(13)(14)(15)(16)(17)(18), and frequently opposite (12)(13)(14)(15)(16)(17)(18) to the observations of Ley et al Note that only three studies stated that the enrolled patients and controls did not take antibiotics in the 3-mo period before sample collection; and all three studies reported an increased Bacteroidetes/Firmicutes ratio in the gut of obese patients (12)(13)(14)19) (Table 1). Our group paid particular attention to proton pump inhibitors and histamine receptor antagonists (14,19) as these agents are known to affect Firmicutes (20).…”
Section: Hypothetical Mechanism 1: Elevated Energy Extraction In the supporting
confidence: 61%
“…In another randomized controlled trial examining the effects of probiotic therapy on NASH patients using Lactobacillus and Bifidobacterium spp. no significant difference in BMI, fasting glucose, cholesterol, or triglyceride was observed between the probiotics treated group and the control (18).…”
Section: Microbiome Intervention In the Treatment Of Nafld/nashmentioning
confidence: 75%
“…Indeed, a few studies have examined dysbiosis in NAFLD ( Table 1). Patients with NASH harbor a lower abundance of Faecalibacterium and Firmicutes (Clostridiales family, Anaerosporobacter) but a higher abundance of Parabacteroides and Allisonella in their fecal microbiome (45). Importantly, it has been reported that improved intrahepatic TG content is related to a lower abundance of Firmicutes and a higher abundance of Bacteroidetes (45) (15).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with NASH harbor a lower abundance of Faecalibacterium and Firmicutes (Clostridiales family, Anaerosporobacter) but a higher abundance of Parabacteroides and Allisonella in their fecal microbiome (45). Importantly, it has been reported that improved intrahepatic TG content is related to a lower abundance of Firmicutes and a higher abundance of Bacteroidetes (45) (15). In support of these studies, pediatric patients with NAFLD showed an increase in Bradyrhizobium, Anaerococcus, Peptoniphilus, Propionibacterium acnes, Dorea, and Ruminococcus and a decrease in Oscillospira and Rikenellaceae (44).…”
Section: Introductionmentioning
confidence: 99%
“…Faecalibacterium prausnitzii также считается противовоспа-лительным компонентом микрофлоры, умень шение ее представленности ассоциировано с риском развития мета-болических нарушений и воспалительных заболеваний кишечника [14]. У пациентов с метаболическим синдро-мом, сахарным диабетом 2-го типа, ожирением доля Faecalibacterium prausnitzii достоверно снижается [15][16][17][18].…”
unclassified